Cyclic Loading Test of Structural Walls with Small Openings - Hyun-Jin Yu (International Journal of Concrete Structures and Materials, 2019)
Abstract This study aimed to investigate the effects of small openings on the structural performance of reinforced-concrete (RC) structural walls. Cyclic lateral loading tests were conducted on five RC walls with an aspect ratio of 2.6 and small openings. The main test parameter was the size of the small openings. The specimens were designed to fail after flexural yielding, considering the typical failure mode of slender RC walls. The structural performances of the test specimens were analyzed based on the test results in terms of the load-carrying capacity (flexural strength), hysteretic behavior, strain distribution, and the size of the openings. The specimens showed flexural yielding regardless of the size of the openings, and the flexural strength and deformation capacity were not significantly affected by the small openings. This result indicates that small openings do not affect the flexural behavior of slender walls if the walls have sufficient shear resistance and the small openings are located away from the extreme compressive end and in the compression zone where compressive stress does not decrease.